Image Noise Preprocessing of Interactive Projection System Based on Switching Filtering Scheme - Lei Yu (Complexity)
The interactive projection systems based on deep images are usually disturbed by the mixed noise. Generally, several filtering methods are used in combination to resolve this problem. Although the hybrid filter can guarantee the accuracy of the image, but the algorithm is complex and time-consuming, which affects the real-time performance of the interactive projection system. In this paper, the switching system method is introduced into the filter for the first time, and an arbitrary switching filter algorithm is proposed and applied to the depth image filtering system based on Kinect sensor. The experimental results demonstrate and validate that the proposed switching filter algorithm not only effectively removes the noise but also ensures the real-time performance of tracking and achieves good target tracking performance, which makes it applicable in various image filtering processing systems.